St Augustine’s Abbey, Canterbury, and the ‘First Books of the Whole English Church’ - Emms, Richard (Studies in church history, 2004)
Early in the fifteenth century, Thomas of Elmham, who grew up in Norfolk and became a monk of St Augustine’s abbey, Canterbury, began to write and illustrate an ambitious history of his monastery. It may be that his interest in history arose from his early years at Elmham, site of the see of East Anglia in late Anglo-Saxon times. This could explain why he became a monk at the oldest monastic establishment in England instead of at the local Benedictine houses, such as Bury St Edmunds, Ely, or Norwich. Clearly he developed his historical interests at St Augustine’s with its ancient books and relics, even though, apart from the chapel of St Pancras and St Martin’s church nearby, pre-Conquest buildings were no longer to be seen.